PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN PERUSAHAAN LISTING SEKTOR PERTAMBANGAN DI BEI YANG MENERBITKAN SUSTAINABILITY REPORT PERIODE 2021-2023 - Senja Putri Auliya Prayoga; Nurul Aini (Jurnal Ilmiah Akuntansi, 2025)
This research aims to analyze the influence of sustainability reports on the financial performance of mining companies registered on the Indonesia Stock Exchange (IDX). Sustainability reports disclose financial performance as the dependent variable and economic, social, and environmental aspects as independent variables. Mining businesses listed on the IDX that produced sustainability reports in accordance with the GRI G4 standard between 2021 and 2023 constitute the population analyzed in this study. This study employed purposive sampling, yielding a sample of 22 companies with a total of 66 firm-years. Multiple linear regression analysis using SPSS 27 was the methodology used in this investigation. The results of this research show that financial performance is substantially affected by different economic factors, environmental, and social factors as a whole.